Reorienting Educational Efforts for Sustainable Development: Experiences from South Asia. (September 2017) - Mathar, Reiner
Rajeswari Namagiri Gorana and Preeti Rawat Kanaujia (Eds), Springer, Netherlands, 2016, 205 pages, US$ 92.35. ISBN 978-94-017-7620-2. Book series: Schooling for Sustainable Developmenthttp://www.springer.com/in/book/9789401776202